Inovasi Video Pembelajaran Interaktif “Peredaran Darah Manusia”melalui Edpuzzle dengan Penambahan Pertanyaan Tertanam untuk Kelas 5 SD (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
The interactive learning video innovation "Human Blood Circulation" through Edpuzzle, with embedded questions, is designed to address the difficulties faced by fifth-grade elementary school students in understanding abstract biological concepts. Science education in elementary schools often encounters challenges in explaining invisible processes, such as the heart's working mechanism and blood circulation, leading students to struggle with comprehension or merely memorize the material. Conventional learning videos tend to make students passive, necessitating media that can transform the learning process into an active one. Edpuzzle, as an educational platform, allows teachers to insert questions at critical points in the video, requiring students to answer before continuing to watch. This innovation aligns with the cognitive development stage of fifth-grade students, who are in the concrete operational stage.The research objectives include product development, validity and feasibility testing, analysis of conceptual understanding improvement, influence on focus and learning independence, and student responses. Media development refers to Mayer's cognitive theory of multimedia and the characteristics of interactive videos according to Heinich et al. Additionally, media development models such as ADDIE and Dick and Carey are discussed. The main benefits of using Edpuzzle include increasing engagement, facilitating real-time formative assessment, and enhancing learning motivation. However, challenges exist such as technology access, teacher readiness, the risk of technology dependency, and long-term evaluation. The practical implications can support digital learning and the transformation of elementary science education.